Impact of obesity on acute complications of catheter ablation for cardiac arrhythmia. (11th February 2022) - Schenker, Niklas; von Blumenthal, Flurina; Hakmi, Samer; Lemes, Christine; Mathew, Shibu; Rottner, Laura; Wohlmuth, Peter; Reißmann, Bruno; Rillig, Andreas; Metzner, Andreas; Willems, Stephan; Ouyang, Feifan; et al.
Abstract: Introduction: The prevalence of obesity is increasing. However, data on the periprocedural complication rate of catheter ablation for arrhythmia in patients stratified by body mass index (BMI) are scarce. Methods: This study included 1000 consecutive patients (age 62.0 ± 14.4 years) undergoing catheter ablation for cardiac arrhythmia. The primary study endpoint was any periprocedural major complication (cardiac tamponade, pseudoaneurysm, arteriovenous fistula, transient ischemic attack, stroke, valve damage, myocardial infarction, or death). Results: The mean BMI was 27.6 ± 5.1 kg/m 2 and the majority of patients were overweight (BMI 25.0–29.9 kg/m 2, 43.4%). A BMI of 30.0–34.9 kg/m 2 (Class I obesity) was present in 177 (17.7%) of patients, a BMI of 35.0–39.9 kg/m 2 (Class II obesity) in 67 (6.7%), and a BMI ≥ 40 kg/m 2 (Class III obesity) in 16 (1.6%). There were 31 major complications (3.1%) and one fatality (0.1%) due to terminal heart failure in a patient undergoing palliative ventricular tachycardia ablation. There was no significant impact of the BMI on the rate of major complications ( p = .495). Compared to normal weight patients, odds ratios for complications in overweight patients, as well as Class I, II, and III obesity were 1.1 (95% confidence interval (CI): 0.8, 1.7), 1.3 (CI: 0.6, 2.6), 1.4 (CI: 0.5, 4.1), and 1.6 (CI: 0.4, 6.3), respectively. Radiation exposure and procedure duration were significantly increased in obese patients ( p < .001 and p = .001, respectively). Conclusion: In this study, obesity did not have a significant impact on the incidence of periprocedural complications after CA for cardiac arrhythmia.